2008
DOI: 10.1039/b710915f
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed nanostructures for surface-enhanced Raman spectroscopy

Abstract: Research on surface-enhanced Raman spectroscopy (SERS) is an area of intense interest because the technique allows one to probe small collections of, and in certain cases, individual molecules using relatively straightforward spectroscopic techniques and nanostructured substrates. Researchers in this area have attempted to develop many new technological innovations including high sensitivity chemical and biological detection systems, labeling schemes for authentication and tracking purposes, and dual scanning-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
656
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(660 citation statements)
references
References 41 publications
1
656
0
3
Order By: Relevance
“…We have also successfully demonstrated that, by using selective functionalization 7 of our doped opals, local changes in the composition and optical properties of these films can be induced. This synthetic methodology can be extended to other types of nanoparticles, such as silver, 52 platinum, 53,54 and palladium, which are easily synthesized and stabilized in aqueous solutions and can lend other important properties to these hybrid 3D nanoporous materials that are beneficial for antimicrobial activity, 52 3D scaffold structures for SERS sensing, [55][56] colorimetric fluid analysis, 57 and catalytic activity. 24 We believe that the robust, large-scale, nanoparticle-doped inverse opals of uniform, tunable and accessible composition synthesized via three-phase co-assembly can find use in a whole range of applications in the fields of photonics, sensing, and catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…We have also successfully demonstrated that, by using selective functionalization 7 of our doped opals, local changes in the composition and optical properties of these films can be induced. This synthetic methodology can be extended to other types of nanoparticles, such as silver, 52 platinum, 53,54 and palladium, which are easily synthesized and stabilized in aqueous solutions and can lend other important properties to these hybrid 3D nanoporous materials that are beneficial for antimicrobial activity, 52 3D scaffold structures for SERS sensing, [55][56] colorimetric fluid analysis, 57 and catalytic activity. 24 We believe that the robust, large-scale, nanoparticle-doped inverse opals of uniform, tunable and accessible composition synthesized via three-phase co-assembly can find use in a whole range of applications in the fields of photonics, sensing, and catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Photonic effects can influence the photoinduced performance of entrapped functional components such as plasmonic nanoparticles. Indeed, efficient surface enhanced Raman scattering (SERS) substrates 253 have been made from colloidal templating due to the enhancement of plasmonic photoexcitation within the partial photonic bandgap. In this section, we focus on sensing applications that rely on structural and chemical changes in CBPM.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…20 Certain NPs with welldefined sharp corners and edges, where hot spots located, would generate much stronger electromagnetic field 20b,21 and exhibit larger plasmonic enhancement factors. 22 Among those intriguing nanostructures listed above, concave cubic NPs are the most interesting, because of their hot spots featuring intensified electromagnetic field as well as extraordinary high chemical activity originating from high-index facets. Despite such distinct optical and chemical properties of concave cubic NPs, there is no report yet on applying such concave nanostructures in photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%